2014
DOI: 10.1590/0100-2945-391/13
|View full text |Cite
|
Sign up to set email alerts
|

Enxertia de fruteira-pão em função da idade do porta-enxerto

Abstract: GRAFTING OF BREADFRUIT IN RELATION TO ROOTSTOCKS AGEaBstract -The study was conducted at the Federal University of Bahia Reconcavo in the municipality of Cruz das Almas, Bahia, Brazil, with the objective of evaluating the effect of the age of rootstock on the method of propagation by grafting. The rootstocks used were obtained from breadfruit tree seeds. A. altilis variety seminifera and grafting method used was the grafting of top cleft when the rootstocks had two, four, six and eight months old. The experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Another factor that may have been aggravating is the age of the rootstocks and according to Santana et al (2014) in studies with breadfruit (Artocarpus altilis) observed that there is influence of the age of the rootstock on the efficiency of the grafting. The rootstocks used in the experiment were eight months older than those used in the first experiment when they were 16 months old.…”
Section: In Avocadomentioning
confidence: 99%
“…Another factor that may have been aggravating is the age of the rootstocks and according to Santana et al (2014) in studies with breadfruit (Artocarpus altilis) observed that there is influence of the age of the rootstock on the efficiency of the grafting. The rootstocks used in the experiment were eight months older than those used in the first experiment when they were 16 months old.…”
Section: In Avocadomentioning
confidence: 99%